2014
DOI: 10.1002/lary.25001
|View full text |Cite|
|
Sign up to set email alerts
|

CPAS: Surgical approach with combined sublabial bone resection and inferior turbinate reduction without stents

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This is the first report of a case of CNPAS in which both inferior turbinate reduction and postoperative stents were utilized. Furthermore, in previously published studies, postoperative nasal stents were left in place for 5 days to a maximum of 4 weeks (Visvanathan and Wynne 2012; Gonik et al 2015; Merea et al 2015). In this patient, we trialed different types of nasal stents for periods of time while the patient was admitted to the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first report of a case of CNPAS in which both inferior turbinate reduction and postoperative stents were utilized. Furthermore, in previously published studies, postoperative nasal stents were left in place for 5 days to a maximum of 4 weeks (Visvanathan and Wynne 2012; Gonik et al 2015; Merea et al 2015). In this patient, we trialed different types of nasal stents for periods of time while the patient was admitted to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one case reported the use of bilateral intranasal mometasone furoate stents, traditionally used following sinus surgery to maintain patency and locally deliver steroid medication, as an alternative to traditional stents, in order to decrease the risk of plugging and nasal alar necrosis (Smith et al, 2017). Inferior turbinate reduction (Merea et al, 2015) has been reported in combination with the above techniques to increase the patency of the nasal cavity. Nasal dilation of CNPAS has also been described in the literature (Wine et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Further, it has also been proposed to perform inferior turbinate reduction rather than stenting at the time of repair. 10 This method could stent open the internal nasal valve and deliver steroids directly to the inferior turbinate. We could also envision using these stents in revision/refractory cases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with stents should be closely followed up due to a risk of restenosis when removed early or tissue necrosis when removed too late. 4 , 6 Merea et al 11 published a series of six patients who underwent the classic sublabial procedure associated with bilateral inferior turbinectomy without stenting. These researchers reported successful follow-up, with no cases of restenosis or septal perforations.…”
Section: Discussionmentioning
confidence: 99%